2016
DOI: 10.1016/j.jcis.2016.03.049
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying mineral surface energy by scanning force microscopy

Abstract: Fundamental understanding of the wettability of carbonate formations can potentially be applied to the development of oil recovery strategies in a complex carbonate reservoir. In the present study, surface energies of representative carbonate samples were evaluated by direct quantitative force measurements, using scanning force microscopy (SFM) at sub-micron scale, to develop a reliable method to predict reservoir wettability. Local adhesion force measurements were conducted on appropriate calcite and dolomite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 39 publications
(43 reference statements)
0
16
0
Order By: Relevance
“…When the brine was diluted, the freshly grown material was dissolved and the stearic acid patches, formerly incorporated into the crystal during the growth phase, were exposed. Sauerer et al [48] measured the surface free energy of calcite and dolomite samples using AFM adhesion force measurements, in order to predict carbonate reservoir wettability. Adhesion forces, between the installed colloidal calcite and dolomite particles on the AFM tip ( Figure 7) and the planar cleaved calcite and dolomite samples, both in air and in the presence of organic solvents (ethylene glycol, bromonaphthalene and heptane) were measured.…”
Section: Atomic Force Microscopymentioning
confidence: 99%
See 1 more Smart Citation
“…When the brine was diluted, the freshly grown material was dissolved and the stearic acid patches, formerly incorporated into the crystal during the growth phase, were exposed. Sauerer et al [48] measured the surface free energy of calcite and dolomite samples using AFM adhesion force measurements, in order to predict carbonate reservoir wettability. Adhesion forces, between the installed colloidal calcite and dolomite particles on the AFM tip ( Figure 7) and the planar cleaved calcite and dolomite samples, both in air and in the presence of organic solvents (ethylene glycol, bromonaphthalene and heptane) were measured.…”
Section: Atomic Force Microscopymentioning
confidence: 99%
“…Carbonate surfaces are originally water-wet, containing positively charged surface electrostatics over a wide range of pH [47]. However, adsorption of negatively charged carboxylic materials (-COO − ), present in the heavy end fractions of crude oil such as resin and asphaltene fractions, onto positively charged carbonate rock surfaces, results in large crude oil particles covering the carbonate surface and could promote mixed-wet or oil-wet characteristics [45,[47][48][49][50]. Carbonate reservoir rocks have inherently higher chemical activities compared to minerals in sandstone reservoirs (quartz); additionally, there have been difficulties in modelling the distribution of permeability in carbonates and predicting reservoir behaviour, due to poor correlation between permeability and porosity.…”
Section: Introductionmentioning
confidence: 99%
“…It has been argued that there may be more than one mechanism, or even an undiscovered mechanism, involved in LSW in carbonates [5]. Although wettability alteration, towards a more desirable state for oil to be recovered, is widely accepted as the main reason to improve oil recovery during LSW [6][7][8][9][10][11], the question of how this alteration happens is still the subject of debate, with no single design fitting all reservoirs. Understanding the wettability mechanism involved in LSW, under controlled laboratory conditions, and the colloidal interactions at oil-rock-brine interfaces are essential in improving the efficiency of LSW.…”
Section: Introductionmentioning
confidence: 99%
“…The magnitude of the adhesion forces for quartz are ranged from 0.021 ± 0.006 μN to 0.032 ± 0.005 μN (Leite et al, 2003) and from 0.015 to 0.060 μN (Jones et al, 2002). Several studies have investigated the adhesive forces for the cleaved calcite crystals immersed in different liquids (Karoussi et al, 2008;Ricci et al, 2015;Røyne et al, 2015;Sauerer et al, 2016;Stipp et al, 1994). To the authors' knowledge, there are a few studies reported in the literature investigating the adhesion forces for calcite at the ambient air conditions.…”
Section: Water Resources Researchmentioning
confidence: 99%